Impact of intensive care unit relocation and role of tap water on an outbreak of Pseudomonas aeruginosa expressing OprD-mediated resistance to imipenem. Issue 3 (November 2018) - Tran-Dinh, A.; Neulier, C.; Amara, M.; Nebot, N.; Troché, G.; Breton, N.; Zuber, B.; Cavelot, S.; Pangon, B.; Bedos, J.P.; Merrer, J.; Grimaldi, D.
Summary: Background: To assess the impact of the incidental relocation of an intensive care unit (ICU) on the risk of colonizations/infections with Pseudomonas aeruginosa exhibiting OprD-mediated resistance to imipenem (PA-OprD). Aim: The primary aim was to compare the proportion of PA-OprD among P. aeruginosa samples before and after an incidental relocation of the ICU. The role of tap water as a route of contamination for colonization/infection of patients with PA-OprD was assessed as a secondary aim. Methods: A single-centre, observational, before/after comparison study was conducted from October 2013 to October 2015. The ICU was relocated at the end of October 2014. All P. aeruginosa- positive samples isolated from patients hospitalized ≥48 h in the ICU were included. Tap water specimens were collected every three months in the ICU. PA-OprD strains isolated from patients and tap water were genotyped using pulse-field gel electrophoresis. Findings: A total of 139 clinical specimens of P. aeruginosa and 19 tap water samples were analysed. The proportion of PA-OprD strains decreased significantly from 31% to 7.7% after the relocation of the ICU ( P  = 0.004). All PA-OprD clinical specimens had a distinct genotype. Surprisingly, tap water was colonized with a single PA-OprD strain during both periods, but this single clone has never been isolated from clinical specimens. Conclusion: Relocation of the ICU was associated with a marked decrease in P. aeruginosa strains resistant to imipenem. The polyclonal character of PA-OprD strains isolated from patients and the absence of tap-water-to-patient contamination highlight the complexity of the environmental impact on the endogenous colonization/infection with P. aeruginosa.